A comparative energy analysis of three electrochromic glazing technologies in commercial and residential buildings. (15th April 2017) - DeForest, Nicholas; Shehabi, Arman; Selkowitz, Stephen; Milliron, Delia J.
Highlights: We model a novel dual-band electrochromic window glazing in three building types. Results are generated for 16 cities to determine energy, cost, and carbon savings. Performance is compared with other static and dynamic window technologies. Results indicate modest savings from novel window in most locations and buildings. Benefits also include darkening to reduce glare and eliminating need for blinds. Abstract: This paper presents a simulation study of three dynamic electrochromic window glazings, including a novel glazing capable of independently modulating its optical properties in both the visible and near-infrared spectrums. This capability allows this so-called "dual-band" technology to actively manage the solar heat and visible light transmitted into a building's interior, and creates the potential for heating, cooling, and lighting savings vis-à-vis competing window technologies. In this study EnergyPlus is used to simulate annual energy performance of the dual-band electrochromic (DBEC) glazing in three building types and 16 U.S. climate regions. The savings potential of DBEC windows are presented relative to a conventional electrochromic glazing; a visibly transparent, near-infrared switching electrochromic glazings; and several static alternatives, including ASHRAE 90-2010 standard compliant windows. Results indicate that the DBEC glazings are capable of outperforming alternatives in a diverse set of locations and building types, including both heating and cooling-dominated regions. Relative to code-compliant static windows, the DBEC is capable of achieving annual primary energy savings between 6 and 30 kW h/ft 2 of window area from reduced heating, cooling, and lighting demand. Relative to other advanced glazings, the savings are significantly lower, ranging from 0 to 1.2 kW h/ft 2 . Regional DBEC energy cost savings versus high performance static windows are presented to identify early potential market entries based on energy savings. Finally, the impacts of widespread deployment of high-efficiency LED lighting on DBEC energy savings potentials are also presented.